The Essence and Functions of the Central Bank Republic of Uzbekistan - Parisoda, Musurmonova; Umida, Nuriddinova; Mahomadrizoevna, Karimova Aziza (Research Parks Publishers, 2023)
this article discusses issues related to the essence and structure of the central bank of the Republic of Uzbekistan. The main purpose, objectives and rights of the bank are stated. The functions of the central bank are outlined and a detailed formulation of each of them is given.